Hubungan Efikasi Diri dengan Resiliensi Akademik pada Siswa SMA Kristen 1 Kupang - Tarong, Ursula Salome; Geradus, Uda; Korohama, Katharina E. P.; Apriliana, I Putu Agus (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
Students are expected to have high self-efficacy. Self-efficacy is a person’s belief in his ability to overcome various situations that arise in his life. Self-efficacy plays an important role in increasing student academic resilience. However, there are still students who procrastinate in submitting assignments, have difficulties dealing with demands or pressure in the learning process, and are less able to adapt to obligations in the academic process at school. This research uses a quantitative approach with a descriptive correlation research type. This research was conducted with a total population of 162 students and a sample of 45 students with a proportionate stratified random sampling method. The data was collected through a questionnaire on self-efficacy and academic resilience. The analysis techniques included descriptive and correlational analysis with the SPSS version 26 program. Our findings show that (1) the self-efficacy of students was in the secure category, with a percentage of 56%, (2) the academic resilience of students is in the strong category with a percentage of 53%. (3) Product moment correlation analysis shows that self-efficacy and academic resilience have a significant correlation with a p-value of 0,002. The Pearson correlation is 0,454, which can be said that the degree of relationship is strong with r-table is 0,301. Hence, it can be interpreted that self-efficacy has a strong relationship to academic resilience in Christian High School students.